Acute exercise-induced changes in hemostatic and fibrinolytic properties: analogies, similarities, and differences between normotensive subjects and patients with essential hypertension - Braschi, Annabella (Platelets (Edinburgh), 2019)
Following acute exercise, normotensive and hypertensive subjects both undergo changes in hemostatic and fibrinolytic properties, but the hypertensive patient's response to exercise is exaggerated and prolonged, exposing them to increased cardiovascular risk during or immediately after unusual and strenuous exercise. Thrombotic complications are triggered by the activation of the autonomic sympathetic nervous system in a pathological milieu characterized by platelet α 2 -adrenergic receptors with increased responsiveness to circulating catecholamine, altered platelet profile and function, abnormal hemostatic parameters, impaired fibrinolytic potential, and endothelial dysfunction. The recovery period is particularly dangerous for triggering adverse cardiovascular events because the balance between the thrombotic and fibrinolytic systems is temporarily shifted toward increased pro-coagulative activity. This review highlights the analogies, similarities, and differences between normotensive and hypertensive subjects regarding the acute exercise-induced changes to the hemostatic and fibrinolytic properties, showing what differentiates essential hypertension from physiological status. Abbreviations : HT, hypertensive; METs, metabolic equivalents; min, minutes; MPA, monocyte-platelet aggregates; NT, normotensive; PAI-1, plasminogen activator inhibitor-1; tPA, tissue plasminogen activator; VO 2 max, maximal oxygen consumption.